An adaptive observer-based switched methodology for the identification of a perturbed sinusoidal signal: theory and experiments - Chen,B; Pin,G; Ng,WM; Lee,CK; Hui,SYR; Parisini,T (IEEE Transactions on Signal Processing, 2014)
This paper deals with a novel adaptive observer-based technique for estimating the amplitude, frequency, and phase of a single sinusoidal signal from a measurement affected by structured and unstructured disturbances. The structured disturbances are modeled as a time-polynomial so as to represent bias and drift phenomena typically present in applications, whereas the unstructured disturbances are modelled as bounded noise signals. The proposed estimation technique exploits a specific adaptive observer scheme equipped with a switching criterion allowing to properly address in a stable way poor excitation scenarios. The estimator's stability properties are analyzed by input-to-state stability arguments. The practical characteristics of the proposed estimation approach are evaluated and compared with other existing tools by extensive simulation trials. Real experimental results are provided as well.